1996
DOI: 10.1177/44.9.8773571
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of acetaldehyde-protein adducts in liver biopsies from alcoholic patients.

Abstract: Acetaldehyde, the first product of ethanol in hepatocytes, can react with protein to form acetaldehyde-protein adducts (APAs). Because it has been suggested that these adducts could be involved in the pathogenesis of ethanol-induced hepatic lesions and in fibrogenesis, we performed an ultrastructural immunohistochemical study to precisely define the cellular and subcellular localization of APAs. A preembedding technique of indirect immunoperoxidase was performed in liver biopsy specimens from eight patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Acetaldehyde protein adducts are detectable in alcohol-related disease-associated inflammation and fibrosis 11,64. Ultrastructural and immunohistochemical staining methods revealed that acetaldehyde adducts are detectable in hepatic stellate cells (HSC) in the context of steatofibrosis or cirrhosis, and in myofibroblasts in zones with bridging fibrosis 65. Liver injury is likely mediated by binding of acetaldehyde to lysine residues and secondary interference with lysine-dependent enzymes such as calmodulin, and also tubulin 11.…”
Section: Adducts Promote Liver Diseasementioning
confidence: 99%
“…Acetaldehyde protein adducts are detectable in alcohol-related disease-associated inflammation and fibrosis 11,64. Ultrastructural and immunohistochemical staining methods revealed that acetaldehyde adducts are detectable in hepatic stellate cells (HSC) in the context of steatofibrosis or cirrhosis, and in myofibroblasts in zones with bridging fibrosis 65. Liver injury is likely mediated by binding of acetaldehyde to lysine residues and secondary interference with lysine-dependent enzymes such as calmodulin, and also tubulin 11.…”
Section: Adducts Promote Liver Diseasementioning
confidence: 99%
“…1,[4][5][6] The appearance of aldehyde-protein adducts in zone 3 hepatocytes has been shown to be a typical feature of alcohol-induced liver disease. 5,7,8 Our previous follow-up studies in ethanol-fed micropigs have shown that the formation of aldehyde adducts in the liver coincide with elevation of serum transaminases and progressive histopathology. 7 High levels of reactive aldehydic products in the liver also appear to be associated with activation of fibrogenesis.…”
mentioning
confidence: 99%
“…It may be speculated that ethanol-induced oxidative stress could also aggravate injurious effects of ethanol in several target tissues through adverse immune responses. To date, the existence of acetaldehyde-and malondialdehyde-derived protein epitopes in tissues have, however, only been demonstrated from the liver ( Halsted et al, 1993;Holstege et al, 1994;Niemela et al, 1991Niemela et al, , 1994Niemela et al, , 1995Paradis et al, 1996). Nevertheless, the fact that the antibodies against oxidant stress derived epitopes consist primarily of IgGs is noteworthy since IgG antibodies are known to be the primary mediators of several harmful immunologic consequences, including activation of the complement system, induction of cytotoxic reactions, and release of tissue-damaging mediators, such as proteases and oxygen radicals (Johnson et al, 1994).…”
Section: Discussionmentioning
confidence: 99%